Examining the nutrition levels and stunting problem in Indonesian children - Fitri Yani Arbie; Rahma Labatjo (AcTion: Aceh Nutrition Journal, 2019)
Stunting is recognised as a critical issue in the developing countries like Indonesia that arises due to nutritional deficiencies. The present research paper is aimed at examining the problem of stunting among the Indonesian children of age group 0 to 5 years. Methods, qualitative study with interpretivism philosophy and descriptive research design. Data analysing is using meta-analysis method. Results, the level of nutrition among the children belonging to poor and rural families is lower as compared to the children belonging to urban and rich families in Indonesia. The key reasons behind increasing rate of stunting problem among the children are insufficient nutrition level, low paternal education and less hygienic living conditions. Conclusions, the major reason for stunting is found to be the low level of proper nutrition provision to the children of 0-5 years within Indonesia. It is proposed that proper nutrition should be provided to the Indonesian children and for this purpose, the rural and low-income families should be provided with proper education, employment and financial support. Stunting harus diakui sebagai masalah kritis pada negara berkembang seperti Indonesia yang muncul akibat kekurangan gizi. Penelitian bertujuan untuk meneliti masalah stunting pada anak-anak Indonesia dari kelompok umur 0 hingga 5 tahun. Metode, penelitian kualitatif dengan filosofi interpretivisme dan desain penelitian deskriptif. Analisis data menggunakan metode meta-analisis. Hasil penelitian menemukan, status gizi pada anak-anak dari keluarga miskin dan pedesaan lebih rendah dibandingkan dengan anak-anak dari keluarga perkotaan dan kaya di Indonesia. Alasan utama dibalik meningkatnya masalah stunting di pada anak-anak adalah asupan gizi yang tidak memadai, rendahnya pendidikan orang tua dan lingkungan yang kurang higienis. Kesimpulan, alasan utama banyak stunting ditemukan karena rendahnya tingkat pemberian nutrisi yang tepat untuk anak-anak 0-5 tahun di Indonesia. Saran, nutrisi yang tepat harus diberikan kepada anak-anak Indonesia supaya permasalahan stunting teratasi, selain itu masyarakat di pedesaan dan berpenghasilan rendah harus diberikan pendidikan yang layak, pekerjaan dan dukungan ekonomi yang memadai.